The Bidirectional Association Between Bullous Pemphigoid and Psoriasis: A Population-Based Cohort Study - Kridin, Khalaf; Ludwig, Ralf J.; Schonmann, Yochai; Damiani, Giovanni; Cohen, Arnon D. (Frontiers in Medicine, 2020)
The risk of developing psoriasis during the course of bullous pemphigoid (BP) is yet to be investigated. We aimed to assess the risk of psoriasis among patients with BP and the risk of BP in individuals with a history of psoriasis. A population-based retrospective cohort study was conducted comparing BP patients (n=3,924) with age-, sex- and ethnicity-matched control subjects (n=19,280) with regard to incident cases of psoriasis. A case-control design was additionally followed to estimate the risk of BP in those with a preceding diagnosis of psoriasis. Adjusted hazard ratios (HRs) and adjusted odds ratios (ORs) were estimated by Cox regression and logistic regression, respectively. The incidence of psoriasis was 1.78 (95% CI, 1.25-2.48) and 0.67 (95%CI, 0.53-0.83) per 1,000 person-years among patients with BP and controls, respectively. Patients with BP were 2.6-fold more likely to develop psoriasis (HR, 2.60; 95%CI, 1.59-4.27) compared to controls. Furthermore, the prevalence of preexisting psoriasis was higher in patients with BP than in control subjects (1.7% vs. 1.1%, respectively; P<0.001). A history of psoriasis was associated with a 50% increase in the risk of BP (OR, 1.53; 95%CI, 1.17-2.02). Patients with a dual diagnosis of BP and psoriasis were younger, had higher prevalence of smoking and hypertension, and were treated more frequently with prolonged systemic and topical corticosteroids when compared to the remaining patients with BP. To conclude, a bidirectional association exists between BP and psoriasis. Awareness of this association may be of great importance for physicians managing patients with BP and psoriasis.